1995
DOI: 10.1029/95jc01279
|View full text |Cite
|
Sign up to set email alerts
|

Recirculation in the lee of complicated headlands: A case study of Bass Point

Abstract: It has been argued in recent papers that the nature of headland and coastal island wakes can be highly dependent on the level of turbulence caused by complicated coastal geometry and bottom topography, as well as on the loss of energy and momentum to the seabed due to friction. A series of field experiments was conducted around Bass Point (a 4‐km‐long headland near Sydney, Australia) using moored current meters and an acoustic Doppler current profiler. The offshore component of currents, measured offshore of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The 2‐D results are consistent with previous numerical and experimental results [ Pattiaratchi et al , 1987; Signell and Geyer , 1991; Davies et al , 1995; Denniss et al , 1995] obtained in the literature with simpler and shallower topography. The main controlling parameter appears to be the equivalent Reynolds number Re f , given by the ratio between advection and bottom friction terms.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2‐D results are consistent with previous numerical and experimental results [ Pattiaratchi et al , 1987; Signell and Geyer , 1991; Davies et al , 1995; Denniss et al , 1995] obtained in the literature with simpler and shallower topography. The main controlling parameter appears to be the equivalent Reynolds number Re f , given by the ratio between advection and bottom friction terms.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…A very large body of literature exists on the phenomenon of coastal current separation and eddy formation behind a cape, in terms of experimental, numerical, and theoretical investigations [e.g., Boyer and Tao , 1987; Freeland , 1990; Geyer , 1993; Denniss et al , 1995; Sadoux et al , 2000]. Many of the previous numerical process studies have focused on eddy formation in shallow water environment, where vertically averaged 2‐dimensional (2‐D) dynamics is appropriate [e.g., Verron et al , 1991; Davies et al , 1995], often considering highly energetic, time‐dependent tidal currents and idealized smooth cape structures [ Signell and Geyer , 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Observations by Black and Gay (1987) and Signell and Geyer (1991) indicate eddies are formed at specific phases in a tidal cycle leading to the term “phase‐eddies.” Denniss et al. (1995) observed that small oscillations at the diurnal frequency in the current generates eddies at the same frequency in the lee of Bass Point, Australia. A similar phase‐locking phenomenon was observed by Chang et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evolution of processes leading to the formation of a headland eddy remain to be fully resolved. The complexity of the coastline and bathymetry (Falconer et al 1986;Falconer & Mardapitta-Hadjipandeli 1987;Pattiaratchi et al 1987;Deleersnijder et al 1992;Denniss et al 1995;Furukawa & Wolanski 1998), bottom friction , unsteadiness of flow (Black & Gay 1987), tidal excursion and current direction Denniss et al 1995), and horizontal eddy viscosity (Black 1989) have all been reported to influence eddy growth, size, shape, and decay in different situations.…”
Section: Introductionmentioning
confidence: 99%